Empowerment of MSME Pilots and Mentoring-Based Tourism Villages: Gunungsari Village, Beji, Pasuruan: Pemberdayaan Rintisan UMKM dan Desa Wisata Berbasis Pendampingan: Desa Gunungsari, Beji, Pasuruan - Indarwati , Risna; Fediyanto , Niko; Sari , Wanda Ardita; Magfiroh , Nailil; Tamariska , Ulya; Wibowo , Sulihing Aji; Al-Amien , Mochammad Sandi; Sandy , Mochammad Septa (Universitas Muhammadiyah Sidoarjo, 2022)
This community service activity carried out in Gunungsari village targets the utilization of tourism potential that is still not developed, namely the natural scenery in Tanah Kas Desa (TKD) and siwalan fruit which is also an icon in this village. The problem is that there is no realization of the TKD utilization plan for tourism and there are concerns of residents over the possibility of losses if they make variations in processed products. The impact is on the income of the village community that has not been maximized. This community service-based service program (PKM) aims to increase the strength of Gunungsari village community about diversifying products and increasing the potential of village tourism. The method used is product manufacturing assistance, initiation of creation of TKD photo area. The results achieved are increased knowledge for the empowerment and optimization of selfie facilities.